2000
DOI: 10.1161/01.atv.20.6.1580
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of National Cholesterol Education Program (NCEP) Step II Diet on HDL Cholesterol, Its Subfractions, and Apoprotein A-I Levels in Hypercholesterolemic Women and Men After 1 Year

Abstract: Abstract-We previously reported that high density lipoprotein cholesterol (HDL-C) decreases more in hypercholesterolemic (HC) women than in HC men ingesting an National Cholesterol Education Program (NCEP)Step II diet for 6 months. We examined these subjects to determine whether the differential HDL-C reduction persists after 12 months and whether it is associated with decreased HDL 2 -C and apoprotein A-I. Subjects were screened from an industrial workforce and were defined as HC if 2 low density lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 62 publications
3
24
1
3
Order By: Relevance
“…3A, B ) and quantifi ed the number of lipid plaques within the imaged region. At 7 dpf, control MO-injected embryos fed either a CD or elevated circulating cholesterol (65)(66)(67)(68)(69)(70). To assess the response of genes associated with lipid homeostasis, we analyzed transcript levels in ldlr SB morphants.…”
Section: Increased Vascular Lipid Accumulation In Ldlr Morphantsmentioning
confidence: 99%
“…3A, B ) and quantifi ed the number of lipid plaques within the imaged region. At 7 dpf, control MO-injected embryos fed either a CD or elevated circulating cholesterol (65)(66)(67)(68)(69)(70). To assess the response of genes associated with lipid homeostasis, we analyzed transcript levels in ldlr SB morphants.…”
Section: Increased Vascular Lipid Accumulation In Ldlr Morphantsmentioning
confidence: 99%
“…A few US studies have also reported that increasing saturated fat, cholesterol and monounsaturated fat intake may be associated with lower rates of ischemic stroke [8] , although these results are controversial [29][30][31] . Neither the Health Professionals Study or Nurses Health Study report a deleterious effect on ischemic stroke with high total fat intake, although total fat intake was associated with intraparenchymal hemorrhage [2,12] .…”
Section: Discussionmentioning
confidence: 90%
“…Multiple observational and interventional studies have shown that diets high in saturated [1,2] and trans -saturated fat [3] increase LDL cholesterol, decrease HDL cholesterol, and increase the risk of myocardial infarction [4][5][6] , while diets high in polyunsaturated and monounsaturated fat have the opposite effect [1] . Largely to limit saturated fat intake, the US Department of Health guidelines recommend that for adults total fat should constitute only 20-35% (max.…”
Section: Introductionmentioning
confidence: 99%
“…In metabolic trials, replacement of saturated fat with carbohydrates produces little change in the total:HDL cholesterol ratio in men [7••] and possibly worsens this ratio in women [23][24][25], though fewer studies in women limit the latter determination. Some experimental evidence suggests that specific saturated fatty acids may have differing lipid effects.…”
Section: Saturated Fatmentioning
confidence: 99%